Efficacy of Ovsynch and Ovsynch Plus Protocol for Improvement of Fertility in Postpartum Sahiwal Cows - Lakher, JP; Awasthi, MK; Khan, JR; Poyam, MR (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was conducted to investigate the efficacy of Ovsynch and Ovsynch plus protocol in postpartum (day 60) Sahiwal  cows (n=18). Animals were randomly divided into three equal groups, viz., Ovsynch group, Ovsynch plus group and Control group.  Animals of group I (n = 6) were treated with traditional Ovsynch protocol. The animals (n = 6) of group II were treated with Ovsynch  plus protocol which consisted of an initial intramuscular injection of eCG (Folligon) @ 250 IU on day 60 postpartum followed 3 days  later by GPG (Ovsynch) protocol. In group-III Control, no treatment was given to animals (n = 6). Treated animals were inseminated  at a fixed time between 14 and 20 hrs after second GnRH injection, irrespective of estrus detection. Blood samples were collected  from each animal on days 50 and 60 postpartum to determine the status of cyclicity in animals based on serum concentrations of  progesterone (P4). A third blood sample was collected on the day of prostaglandin treatment to determine the response of first  GnRH injection. Four animals each were cyclic, and two were acyclic in both treatment groups. Four animals each responded to first  GnRH treatment in both treatment groups. Similarly, two animals each got conceived giving conception rate of 50% (2/4) in each treatment. In the control group, one out of 6 animals  got conceived yielding 16.66 % conception rate (1/6) during the study period. It may be thus concluded that Ovsynch and Ovsynch  plus protocol may be used during the early postpartum period to improve the reproductive efficiency in postpartum Sahiwal cows.
Keywords: Conception; Ovsynch; Ovsynch plus; Postpartum; Progesterone; Sahiwal cows